Executing your strategy : how to break it down and get it done - Morgan, Mark; Levitt, Raymond E.; Malek, William A. (Boston, Mass. : Harvard Business School Press, 2007)
In Executing Your Strategy, Mark Morgan, Raymond Levitt, and William Malek show you how to overcome the barriers of failing strategies in your organization. The authors identify the six INVEST imperatives that will enable you to do the right strategic projects - and to do those projects right.
Includes bibliographical references (p. 263-270) and index.
rua 06/06/13
Loans
Keywords: Strategic planning; Project management; Organizational effectiveness; Leadership